Pembangunan Infrastruktur Jembatan Musi VI Kota Palembang Pemembebasan Lahan - Jannah, Miftahul; Minako, Muchlis (Indonesian Journal of Social Development, 2023)
Agrarian conflict is an unavoidable conflict related to land and its management. One form of agrarian conflict is manifested in land acquisition disputes for the construction of alternative road infrastructure in the Iliri region, namely the 35 Iliri area of Palembang. This conflict is related to the amount of compensation given by the government whose calculation is not in accordance with the affected communities, and there are other land acquisition conflicts. The purpose of this study was to determine the forms, processes and socio-cultural factors that support and hinder the process of resolving land acquisition conflicts in 35 cities of Ilir Palembang.